2018
DOI: 10.1590/1678-457x.23217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage conditions on phytochemical and stability of purple corn cob extract powder

Abstract: Recently, purple corn cob has been gaining popularity for a dietary supplement and natural colorant. However, phytochemicals in waxy purple corn cob (WPC) are likely degraded during storage; thus, the microencapsulation by spray drying was used for lengthening those compounds. This work focused on the phenolic and anthocyanin content and antioxidant activity (ADA) in WPC extract microcapsules by hydroxypropyl beta-cyclodextrin (HPβCD) during storage at 4 and 30 °C for 60 days. The results revealed that only pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…Based on this comparison, the freshly prepared extracts had a significantly higher inhibition percentage than the stored ones, where anticancer inhibition decreased around 19% for HeLa and 10% for the breast cancers. The results showed that storage conditions could affect stability as well as anticancer activity of extracts, with antioxidant activity found in the extracts might be slightly non-optimal 54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this comparison, the freshly prepared extracts had a significantly higher inhibition percentage than the stored ones, where anticancer inhibition decreased around 19% for HeLa and 10% for the breast cancers. The results showed that storage conditions could affect stability as well as anticancer activity of extracts, with antioxidant activity found in the extracts might be slightly non-optimal 54 .…”
Section: Resultsmentioning
confidence: 99%
“…The liposome is biodegradable and could hold extracts inside by utilizing hydrophobicity of extract, while ingestion or injection to bloodstream could be done without any risks of destroyed nanoparticle carrier. It was also reported that a simple spray-drying and cyclodextrin coating could stabilize the antioxidant activity of phenolic compounds, which might be ideal for increasing shelf-life and biocompatibility with the human body 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Although, it was lower at temperatures above 80 °C and times of 10 min. The degradation of anthocyanins from various sources has studied such as blueberry (Song et al, 2018), purple corn (Kapcum and Uriyapongson, 2018), black carrot (Kirca et al, 2007), purple potatoes (Qiu et al, 2018), where it is reported that anthocyanin degradation is greater at high processing or storage temperatures and its degradation increases with longer treatment times. Also, Kirca et al (2007) found that the greatest degradation of anthocyanins occurs at a pH greater than 3 and temperatures between 70 and 90 °C.…”
Section: Monomeric Anthocyanin Contentmentioning
confidence: 99%
“…Black rice ( Oryza sativa L.) and purple corn ( Zea mays L.) have been described as novel sources of natural antioxidants. They are rich in anthocyanins and phenolic compounds [ 21 , 22 ], which play a role as antioxidant that their structure can be able to donate electrons to the free radicals with unpaired electrons and reduce agents in the electron-transfer reaction pathway [ 23 ]. Antioxidant activity of anthocyanin also increased desaturase enzymes activity for converting monounsaturated fatty acid (MUFA) to polyunsaturated fatty acid (PUFA) or inserting additional unsaturated bonds into already existing PUFA [ 24 ].…”
Section: Introductionmentioning
confidence: 99%